TEXT IS A HIGH-LEVEL SYNTACTIC UNIT - Turniyazova Shakhnoza Nigmatovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article deals with the linguistic status of the text, views on text analysis, syntactic analysis of the text. Thoughts on syntactic semantics are given. In particular, it provides theoretical information that syntactic semantics does not only study the semantic weight of the text, but also analyzes the semantic weight of the text, checks the interpretation of issues such as the completeness of the text, the logical integrity. At the same time, a wide range of the subject of the study of syntactic semantics of texts is considered, while the syntax is directly related to the fact that the object of examination is not only a small syntax, but also a large syntax.